Q&A of liquid crystal alignment: theory and practice - Muravsky, Alexander; Murauski, Anatoli (Frontiers in Soft Matter, 2024)
We selected and summarized the most important aspects of liquid crystal alignment. Alignment by the surface profile and flat surface alignment are discussed as the main factors leading to high quality orientation of liquid crystals. The advanced level of understanding and formulation allows linking the alignment layer properties to the molecular structure of the alignment material. The paper reviews and combines the latest knowledge on liquid crystal alignment, dwells upon the relationship between the polar and azimuthal anchoring energy, explains the major particularities regarding anchoring measurements in the case of birefringent alignment materials with truly high azimuthal anchoring energy and observes the current trends of water-friendly alignment materials and its application for geometrical phase devices fabrication.